COST–BENEFIT ANALYSIS AS AN UNDERUSED MECHANISM IN MACEDONIA CASE STUDY: PUBLIC URBAN TRANSPORT IN TETOVO - Merita MUSTAFAI; Verica DANCEVSKA; Elmir MUSTAFAI (International Scientific Journal in Economics, Finance, Business, Marketing, Management and Tourism-ECONOMIC VISION, 2026)
Transport is a crucial factor in the modern economy. But there is constant conflict in society regarding the choice of priorities and the decision to favor one project over another (Button, 2010; Banister, 2008) Cost–Benefit analysis (CBA) is a standard economic tool for evaluating infrastructure and transport projects in European Union countries (European Commission, 2014; Boardman et al., 2018). However, in the Republic of North Macedonia, its application in planning and implementing public transport projects is very limited, that is, it is rarely used as an economic tool in the evaluation and decision-making process. The aim of this paper is to present the significance and applicability of CBA through an analysis of a proposed model of organization of public urban transport in the city of Tetovo. By defining costs and benefits and calculating basic economic indicators, the paper shows that CBA can provide a relevant basis for making rational and transparent decisions in transport planning (Mackie et al., 2014; World Bank, 2020).